ANALISIS PERHITUNGAN PAJAK PENGHASILAN PASAL 23 DAN PAJAK PERTAMBAHAN NILAI ATAS JASA PENGANGKUTAN PADA PT. ANUGERAH KREASI SELARAS MEDAN - Andini, Retno Putri; Septriawan, M. Reza; Marviana, Ratna Dina (Worksheet : Jurnal Akuntansi, 2024)
The duty to pay the taxes of Anugerah Kreasi Selaras Medan pursuant to the established rate, with a reduction of the income tax of Article 23 of 2% of the tax base. (DPP). Respect for payments and reporting reflects professionalism, social responsibility, and positive contributions to economic development. Focus on the tax cuts, calculation, and reporting aspects of the Harmonized Creative Awards, related to Value Added Tax (PPN). Despite a VAT rate of 11%, the company exempts VAT on transport services under government regulations. And regardless of the purpose of this study, How the calculation, reduction, and deposition of income tax and value added tax on PT. And despite payments being delayed for several months due to falls on Sunday, the company is still showing good faith. PT Anugerah Kreasi Selaras adheres to the cut-off exemption rules for service companies with tax-free declarations.Annual evaluation shows an increase in the amount of DPP and VAT owed paid. The VAT exemption on transport services is aimed at keeping land transport tariffs affordable to the public and encouraging economic growth and job creation. The positive impact involves strengthening the public transport sector and preventing the transition of the public to other modes of transport that may occur as a result of the increase in tariffs due to the burden of VAT